2020
DOI: 10.1109/access.2020.3017788
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Stress and Dynamics Analysis of a High-Speed Permanent Magnet Machine for a Micro Gas Turbine Considering Multiphysics Factors

Abstract: For high-speed permanent magnet machines (HSPMMs), the precise analysis of rotor stress and rotor dynamics is essential to ensure the stable operation of rotor under high-speed conditions. This work conducts an in-depth research on the rotor of an HSPMM for a micro gas turbine with predetermined geometrical sizes. Firstly, the mechanical and electromagnetic losses are investigated by both, empirical methods and finite element method (FEM) respectively, and then the 3D steady-state temperature distribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It was found that the error caused in the natural frequencies by neglecting the thermal expansion effect can be 4%. M. Zheng et al analysed the thermal expansion effect on the natural frequencies of a micro gas turbine rotor system with a surface mounted permanent magnet machine [16]. The carbon fibre wrapping direction impact was considered in the thermal stress analysis.…”
Section: A Load Modelling In Rotating Electrical Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the error caused in the natural frequencies by neglecting the thermal expansion effect can be 4%. M. Zheng et al analysed the thermal expansion effect on the natural frequencies of a micro gas turbine rotor system with a surface mounted permanent magnet machine [16]. The carbon fibre wrapping direction impact was considered in the thermal stress analysis.…”
Section: A Load Modelling In Rotating Electrical Machinesmentioning
confidence: 99%
“…Some more specific results are also notable such as use of cast aluminium which doesn't seem to be an appropriate choice due to degradation of mechanical properties. (16). Note that the stiffness of 3.61e07 N/m is adopted for the three design options.…”
Section: Case Studymentioning
confidence: 99%
“…Stress computation techniques are categorized into finite element and analytical analysis. [22], [23] use the finite element method, while numerous other research articles proposed an analytical computation model [24]- [29]. [24] suggested a simplified analytical approach based on the premise that the rotor is severely rotational symmetry.…”
Section: Figure 1 Proposed Rotor Topologymentioning
confidence: 99%
“…[22], [23] use the finite element method, while numerous other research articles proposed an analytical computation model [24]- [29]. [24] suggested a simplified analytical approach based on the premise that the rotor is severely rotational symmetry. The displacement technique was proposed for the computation of a high-speed PM machine with a non-magnetic alloy enclosure [25] and [26].…”
Section: Figure 1 Proposed Rotor Topologymentioning
confidence: 99%
“…The heating condition of an ordinary motor may be relatively low, but the heating condition of a high-speed motor is serious due to the higher speed and greater power. The temperature has a great impact on the stability of a high-speed motor [18][19][20]. It is valuable to focus on the relationship between temperature and rotor strength of a high-speed motor.…”
Section: Introductionmentioning
confidence: 99%